Effect of particulate reinforcement on wear behaviour of aluminium matrix composites - Korkut, MH (Sage Publications Inc, 2004)
The friction and wear behaviour of aluminum matrix composites reinforced with particulates of M7C3, SiC, SiFe, Al2O3 and SiFe - Al2O3 was investigated under various loads and temperatures. Wear tests were conducted under dry sliding conditions using a pin on disc apparatus. Results of the investigations indicated that the coefficient of friction and wear rate of the composites were lower than those of pure aluminium, and the difference between the friction coefficient and wear rate of the composites and those of pure aluminium was enhanced with an increase in load and in contact temperature. The type of reinforcement did not significantly influence the wear and friction properties of the composites. However, the volume fraction of reinforcement affected the wear rate excessively. Nevertheless, it was seen that both coefficient of friction and wear rate behaviours of the composites were approximately similar.
Keywords: aluminium matrix composites; wear